Avaliação das classificações histopatológicas e da expressão por imuno-histoquímica das proteínas E-caderina e B-catenina no Carcinoma de células escamosas bucal - Lindenblatt, Rhayany de Castro (2008)
TNM System has been used for many decades in an attempt to predict clinical behavior and therapy for oral squamous cell carcinomas (OSCC). Studies demonstrate that histopathologic grading systems can be important as predictive factors. In OSCC, the expression of E-cadherin and B-catenin has been associated with increased invasiveness and unfavorable prognosis. The aim of this study was to apply histopathologic classifications of Anneroth et al. (1987), Bryne et al. (1992), WHO grading system (2005) and Brandwein-Gensler et al. (2005) and to analyze the expression of E-cadherin and B-catenin in primary OSCC. The records of 53 patients diagnosed with primary OSCC in INCa during the year of 1999 were reviewed. Most of the sample was composed of men (81%) between 60 and 70 years old (67.4%). Floor of the mouth and tongue accounted for 49.1% and 47.2% of the cases, respectively. Clinical stage I and II accounted for 56.6% of the tumors, while in the pathologic stage analysis 50.9% of the tumors were in stage III and IV. Histophatological analysis was performed using the parameters of each classification studied. Immunohistochemical staining method was used to evaluate the expression of E-cadherin and B-catenin. Survival analysis was performed through Kaplan-Meier method and log rank test. A p value <. 05 was considered to indicate statistical significance. Statistical program for Social Sciences (SPSS) computer software was used for all analysis. 83% of the tumors were moderately differentiated (WHO) and 52.8% were of intermediate risk (Brandwein-Gensler). Both Anneroth and Bryne et al. presented mostly intermediate prognosis cases (45.3% and 50.9% respectively). Anneroth classification was statistically associated with pathologic stage (0.02, chi-square) and lymph nodes involvement (0.0009, log rank test). WHO grading system was related to recurrence (0.043, chisquare) and also to disease-free survival (0.031 log rank test). Brandwein-Gensler et al. risk assessment was statistically associated with overall, disease-free and specific survival (0.015; 0.037; 0.029 log rank test). Bryne s grading failed to show statistically significant associations. Descriptive analysis showed that E-cadherin expression was related to lymph nodes involvement (0.019, chi-square), overall survival (0.044 log rank test) and Brandwein-Gensler classification (0.047, chi-square). At immunohistochemical quantification, the sample obtained values lower than the median value for both proteins and showed a significant association with specific survival for E-cadherin (0.047 log rank test). In addition, there was a significant association between B-catenin and WHO grading system (0.04, chi-square). In conclusion, loss or reduction of E-cadherin and B-catenin is involved in the process of oral carcinogenesis, mainly in the invasion and metastasis of oral squamous cell carcinoma